2020
DOI: 10.1007/s00134-020-06267-0
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 in critical care: epidemiology of the first epidemic wave across England, Wales and Northern Ireland

Abstract: To describe critical care patients with COVID-19 across England, Wales and Northern Ireland and compare them with a historic cohort of patients with other viral pneumonias (non-COVID-19) and with international cohorts of COVID-19. Methods: Extracted data on patient characteristics, acute illness severity, organ support and outcomes from the Case Mix Programme, the national clinical audit for adult critical care, for a prospective cohort of patients with COVID-19 (February to August 2020) are compared with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
126
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 24 publications
20
126
4
3
Order By: Relevance
“…Larsson and colleagues [7] reported on the characteristics and outcomes of 260 patients admitted to ICU at the Karolinska Institute in Stockholm, although almost one quarter of patients did not have a completed ICU episode at the time of analysis and their study lacked detailed information on physiological variables and treatments received on ICU. The UK Intensive Care National Audit and Research Centre (ICNARC) has published regular reports throughout the pandemic [16], summarised in a recent peer-reviewed publication [18]. These analyses have been limited to physiological data from the first 24 hours of admission and have lacked detailed information on symptoms and disease-specific therapies received on ICU, such as prone position ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Larsson and colleagues [7] reported on the characteristics and outcomes of 260 patients admitted to ICU at the Karolinska Institute in Stockholm, although almost one quarter of patients did not have a completed ICU episode at the time of analysis and their study lacked detailed information on physiological variables and treatments received on ICU. The UK Intensive Care National Audit and Research Centre (ICNARC) has published regular reports throughout the pandemic [16], summarised in a recent peer-reviewed publication [18]. These analyses have been limited to physiological data from the first 24 hours of admission and have lacked detailed information on symptoms and disease-specific therapies received on ICU, such as prone position ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of comorbidities was high, with only 16% reporting no past medical history. Data from all ICUs in England, Wales, and Northern Ireland, as reported by ICNARC [18], found that 70% of patients were male, 74% were overweight or obese, and 36% were from ethnic minorities, with a median age of 60. These findings closely mirror those seen at our institution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations